2019
DOI: 10.1101/570333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain Age Prediction: Cortical and Subcortical Shape Covariation in the Developing Human Brain

Abstract: Cortical development is characterized by distinct spatial and temporal patterns of maturational changes across various cortical shape measures. There is a growing interest in summarizing complex developmental patterns into a single index, which can be used to characterize an individual's brain age. We conducted this study with two primary aims. First, we sought to quantify covariation patterns for a variety of cortical shape measures, including cortical thickness, gray matter volume, surface area, mean curvatu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 56 publications
(65 reference statements)
3
17
1
Order By: Relevance
“…Other methods, such as structural learning and integrative decomposition of multi-view data (47), common orthogonal basis extraction (48), and group factor analysis (49), may also be used. Our results suggest that an attractive feature of JIVE is the performance robustness, consistent with our prior study of brain age prediction (20).…”
Section: Structural Covariation May Reflect Synchronized Developmentsupporting
confidence: 90%
See 2 more Smart Citations
“…Other methods, such as structural learning and integrative decomposition of multi-view data (47), common orthogonal basis extraction (48), and group factor analysis (49), may also be used. Our results suggest that an attractive feature of JIVE is the performance robustness, consistent with our prior study of brain age prediction (20).…”
Section: Structural Covariation May Reflect Synchronized Developmentsupporting
confidence: 90%
“…In contrast, JIVE summarizes structural covariation patterns across multiple morphological measures into different component scores. Since brain structures with larger loading magnitudes in a JIVE component are generally more correlated than those with smaller loading magnitudes in the same component (20), the JIVE component scores may provide insight into the extent of synchronized development across brain regions and morphological measures at individual levels. Indeed, our prior work has shown that JIVE can be used to integrate multiple morphological measures into joint and specific components that can robustly predict brain age (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two techniques have yet to be utilized in neurosubtyping but recent neuroimaging studies support their utility in predicting brain age or brain relationship with demographics and behavior (95,96), as well as of extracting a low-dimensional representation of depression-related connectivity (97).…”
Section: Diagnostic Samplesmentioning
confidence: 99%
“…20 Using random forest regression trained on data from 50 healthy individuals, Shahab and colleagues showed that patients with schizophrenia (n=81) had a mean brainPAD of 7.8 years. 21 Other regression algorithms commonly used to estimate brain-age in neuropsychiatric conditions include ordinary least squares (OLS) regression, 22,23 least absolute shrinkage and selection operator regression (Lasso), 24,25 ridge regression, 26,27 and elastic-net regression. 28 At present, it is unclear whether the performance of these machine learning approaches is comparable when estimating brainPAD.…”
Section: Introductionmentioning
confidence: 99%